PENGARUH CITRA MEREK DAN KUALITAS BENIH TERHADAP KEPUTUSAN PEMBELIAN PADA PT.PRABU ARGO MANDIRI (Studi Kasus Penjualan Benih Tomat Merk Maya di Purwkarta) - Ahmad Iskandar (JURISMA : Jurnal Riset Bisnis & Manajemen, 2016)
In the era of globalization, the competition in the business world becomes very tight. Companies vying to be able to continue to compete and survive in the business world. Each consumer must have had the expectation that the products they buy are able to provide satisfaction for them to be making purchasing decisions. Consumer purchasing decisions of companies to seeds virtual brand still low due to the brand image and quality of seeds that are still unsatisfactory.This study aims to determine the responses of respondents regarding brand image, product quality, purchasing decisions and how big an impact on the brand image itself against purchase decisions on the PT. Prabu Argo Mandiri Bandung and how much influence the quality of products on the purchase decision.The method by which the samples is Simple Random Sampling consists of 80 respondents. The method of analysis in this research using descriptive analysis and verification which is composed of multiple linear regression analysis. Product moment correlation analysis, and the coefficient of determination used to measure the level of influence of brand image and product quality on purchasing decisions.The results based on descriptive analysis of brand image variable is in good enough category, variable quality of the product is in the unfavorable category, and the purchase decision variable is in the unfavorable category. The results based on correlation test showed that the brand image is partially significant effect on purchasing decisions by 68% and the product quality is partially significant effect on purchasing decisions by 13%. Hypothesis test results suggested that the increased purchasing decisions partially and simultaneously influence through brand image and product quality.